RELIABILITY ANALYSIS OF FAILURE RELATED MECHANICAL PARTS BASED ON VINE COPULA MODEL - HU QiGuo; ZHOU Song (Jixie qiangdu)
Aiming at mechanical parts for multi-failure modes,the advantages of using Copula functions to describe correlations,a reliability modeling method for multi-failure mode related mechanical parts is proposed. Based on the Vine Copula function,the reliability problem of mechanical parts related to complex and multi-failure is transformed into the analysis of multiple two-dimensional Copula functions,optimal two-dimensional Copula function is identified by using maximum likelihood estimation and AIC information criterion. Mechanical parts failure mode is relatively small,access to less failure samples. To avoid the variability of AIC values,based on improved parameters is proposed to identify the optimal two-dimensional Copula function when the failure sample size is small. The feasibility of the improved parameter Bootstrap method is verified by Matlab simulation,then the reliability of the multi-failure mode related mechanical parts is solved by using the Vine Copula model.Finally,through the comparison between the calculation example of drive shaft and other methods,the method is rationality and validity.